2017
DOI: 10.1109/tit.2016.2615627
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Transmit Correlation Diversity in Multiuser MIMO Systems

Abstract: Correlation across transmit antennas, in multiple antenna systems (MIMO), has been studied in various scenarios and has been shown to be detrimental or provide benefits depending on the particular system and underlying assumptions. In this paper, we investigate the effect of transmit correlation on the capacity of the Gaussian MIMO broadcast channel (BC), with a particular interest in the large-scale array (or massive MIMO) regime. To this end, we introduce a new type of diversity, referred to as transmit corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 53 publications
0
57
0
Order By: Relevance
“…A potential issue of the conventional M -dimensional MMSE channel estimation is ... In terms of computational complexity 2) (Intra-Cell) Non-Orthogonal Pilot Scheme: It is known [3], [8] that the conventional orthogonal pilot scheme may significantly limit the sum-rate performance of MU-MIMO systems unless max K is smaller than T c /2. To overcome this limiting factor, we also consider the non-orthogonal pilot scheme.…”
Section: Low-dimensional Channel Estimationmentioning
confidence: 99%
“…A potential issue of the conventional M -dimensional MMSE channel estimation is ... In terms of computational complexity 2) (Intra-Cell) Non-Orthogonal Pilot Scheme: It is known [3], [8] that the conventional orthogonal pilot scheme may significantly limit the sum-rate performance of MU-MIMO systems unless max K is smaller than T c /2. To overcome this limiting factor, we also consider the non-orthogonal pilot scheme.…”
Section: Low-dimensional Channel Estimationmentioning
confidence: 99%
“…In stark contrast, a different set of investigations has shown that correlation can enhance MU-MIMO performance [11][12][13][14][15][16][17][18][19][20]. Collectively, a critical observation from these studies is that the departing spread of electromagnetic energy from the BS can arrive at the terminals with substantially different power angular spectra, leading to variations in the channel statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Such models are characterized in terms of the mean direction-of-arrival (DOA) at a terminal, angular spread of departure, as well as the antenna spacing at the BS. The authors of [11,12] utilized the one-ring model to group the terminals with similar correlation characteristics in order to motivate the joint spatial division multiplexing technique. The study in [14] shows that if correlation matrices span orthogonal subspaces, pilot contamination can vanish, allowing the ergodic spectral efficiency to grow without bound with increasing numbers of BS antennas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When time-division duplexing (TDD) is employed, downlink CSI can be extracted from uplink signals using the channel reciprocity. However, since frequency-division duplexing (FDD) is used in most existing cellular systems, effective CSI feedback schemes need to be developed to minimize the feedback overhead while maintaining high system throughputs [4]- [12].…”
Section: Introductionmentioning
confidence: 99%